Experimento sonoro : inter-relações entre Django e Django Livre - Araújo, Paulo Victor Gurgel de (2022)
This research makes a comparative analysis of two feature films side-by-side focusing on discussing the characteristics that approximate and differentiate them between their environment sounds. On the one hand, Django Unchained (2012), made in a contemporary context and directed by Quentin Tarantino. On the other, Django (1966), a classic of Italian western cinema, directed by Sérgio Corbucci. Films relate to each other in many ways, from their narrative contexts to a metalinguistic relationship. Tarantino uses the resource of pastiche to insert your work inside the western aesthetics, using elements from Corbucci film. Some of the sounds in the most recent job are the result of experiences after the space-time context in which the work takes place, making image and sound establish an anempathetic relationship. As a result of this approximation, it was possible to analyze and build the Sound Experiment uniting the two works. The purpose of the experimentation is to generate a device that helps the sound perception though the act of differentiate the original sequences from those that had its audio manipulated.